Access to silicon(II)- and germanium(II)-indium compounds - Pahar, Sanjukta; Karak, Suvendu; Pait, Moumita; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2018)
Despite the remarkable ability of N-heterocyclic silylene to act as a Lewis base and form stable Lewis adducts with group 13 elements such as boron, aluminum, and gallium, there has been no such comparable investigation with indium and the realization of a stable silylene-indium complex has still remained elusive. Similarly, a germylene-indium complex is also presently unknown. We describe herein the reactions of [PhC(NtBu)(2)SiN-(SiMe3)(2)] (1) and [PhC(NtBu)(2)GeN(SiMe3)(2)] (4) with InCl3 and InBr3 that have resulted in the first silylene-indium complexes, [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InCl3] (2) and [PhC(NtBu)(2)Si{N(SiMe3)(2)}-> InBr3] (3), as well as the first germylene-indium complexes, [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InCl3] (5) and [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> InBr3] (6). The solid-state structures of all species have been validated by single-crystal X-ray diffraction studies. Note that 5 and 6 are the first structurally characterized organometallic compounds that feature a Ge-In single bond (apart from the compounds in Zintl phases). Theoretical calculations reveal that the Si(II)-> In bonds in 2 and 3 and the Ge(II)-> In bonds in 5 and 6 are dative bonds.